2000
DOI: 10.1161/01.res.86.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning Activates MAPKAPK2 in the Isolated Rabbit Heart

Abstract: Abstract-Recent studies suggest that p38 mitogen-activated protein kinase (MAPK) may be involved in ischemic preconditioning (PC). To further test this possibility, the regulation of MAPK-activated protein kinase 2 (MAPKAPK2), a kinase immediately downstream from p38 MAPK, and the activity of c-Jun NH 2 -terminal kinase (JNK), a second MAPK, were examined in preconditioned hearts. Isolated, perfused rabbit hearts were subjected to 20 to 30 minutes of global ischemia. Ventricular biopsies before treatment and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
113
1
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 62 publications
8
113
1
1
Order By: Relevance
“…In the current study, we also observed a sevenfold increase in JNK phosphorylation following ischemia-reperfusion. This increase in JNK phosphorylation appears to be mediated by reperfusion and not by ischemia, as a modest decline in JNK activity was observed after 30 min of global ischemia in rat hearts (27). Moreover, ischemia per se for 30 or 45 min failed to activate JNK, but reperfusion was associated with a gradual activation of JNK (35).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the current study, we also observed a sevenfold increase in JNK phosphorylation following ischemia-reperfusion. This increase in JNK phosphorylation appears to be mediated by reperfusion and not by ischemia, as a modest decline in JNK activity was observed after 30 min of global ischemia in rat hearts (27). Moreover, ischemia per se for 30 or 45 min failed to activate JNK, but reperfusion was associated with a gradual activation of JNK (35).…”
Section: Discussionmentioning
confidence: 85%
“…In rat hearts subjected to 20 min of global ischemia, MAPK-activated protein kinase-2 (MAPKAPK2), a kinase immediately downstream from p38 MAPK, activity did not change (27). In rabbit or canine models, ischemia alone caused only a moderate but transient increase in p38 MAPK activity whereas ischemia followed by reperfusion caused a persistent elevation in p38 MAPK activity with maximal activation being reached 10 -15 min after reperfusion (22,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the description of IP by Murry et al [2] in 1986, many researchers have attempt to disclose the mechanisms and directions of this phenomenon [3][4][5][6][7][8][9][10]. If the IP is considered the most powerful known natural form of cardioprotection in experimental research [3], why not use this powerful protective mechanism in heart surgery?…”
Section: Discussionmentioning
confidence: 99%
“…Nakano et al [7] showed that the translocation of PKC is related to activation of mitoK + ATP channel through the stimulation of kinases positioned just below the mitogenic-activated protein kinase p38 (MAPK). The regulation of mitochondrial volume and transport of electrons are the main mechanisms responsible CO 2 ).…”
Section: Introductionmentioning
confidence: 99%